The combination of Ambon banana juice and dates increases maternal weight and estimated fetal weight for the prevention of stunting - Herningsih, Sari; Karo, Marni Br; Lumbansiantar, Rupdi (PT. Mega Science Indonesia, 2025)
Stunting is a form of chronic malnutrition that begins during the prenatal period. Nutritional interventions during pregnancy play a role in preventing fetal growth retardation. Ambon bananas (Musa acuminata) and dates (Phoenix dactylifera) contain iron, folate, and micronutrients that support maternal health and promote fetal growth. This study aimed to evaluate the effectiveness of a combination of Ambon banana and date juice in increasing maternal weight and estimated fetal weight in third-trimester pregnant women as a stunting prevention measure. A quasiexperimental study with a pretest‒posttest control group design was conducted with 20 pregnant women in their third trimester at the Imas Masriyah Midwife Practice, Bogor Regency, Indonesia, from October to December 2023. The respondents were divided into an experimental group (n=10) that received Ambon banana and date juice and a control group (n=10) without any special intervention. Maternal weight and estimated fetal weight were measured before and after the intervention. Data analysis was performed via paired t-tests. In the experimental group, the mean maternal weight increased from 54.90±3.071 kg to 56.40±2.989 kg (p=0.003), and the estimated fetal weight increased from 2.43±0.155 kg to 2.58±0.152 kg (p=0.005). The control group showed no significant changes in maternal weight (p=0.022) or estimated fetal weight (p=0.036). The combination of Ambon banana juice and dates effectively increased maternal weight and estimated fetal weight in pregnant women in the third trimester and has the potential to be used as a nutritional intervention for stunting prevention.